Integrated photovoltaic thermal systems, their applications and recent advance on performance improvement: a review. Issue 5 (3rd September 2021) - Shakeriaski, Farshad; Ghodrat, Maryam; Salehi, Fatemeh
ABSTRACT: The current paper presents a review of recent studies on photovoltaic thermal (PV/T) systems to understand the effect of performance parameters. PV/T systems make electricity and store thermal energy; simultaneously and hence they enhance the overall efficiency. Despite significant progress in improving the performance of these technologies, there is still a lack of efficiency and functionality in transforming solar energy into electricity. In this paper, we focus on different effective parameters that affect the efficiency of photovoltaic/thermal systems. Based on existing research streams, there are three main objectives to investigate PV/T systems: (i) analysing existing technologies, (ii) exploring performance barriers and factors influencing PV/T efficiency, and (iii) studying the maintenance issues. In addition, this paper reviews integrated photovoltaic thermal systems which offer a solution for heat lost due to the significant influence of operating temperature on the photovoltaic panel efficiency.